PENGUATAN SINYAL GLOBAL SYSTEM FOR MOBILE COMMUNICATION (GSM) 900 MHz MENGGUNAKAN ANTENA GRID - Afrizal Yuhanef (Teknik Elektro Politeknik Negeri Padang, 2013)
The antenna is a device used to transmit or receive electromagnetic waves electromagnetic waves. Reception using an antenna will amplify the signal acquisition in accordance with the ability of the antenna itself. Service providers GSM (Global System Mobile), with the inclusion of the network limitations make the need for strengthening the acquisition of the signal is very large. Grid antenna is one option reinforcement signal acquisition. Grid antenna has a major component that is driven in the form of a dipole and a reflector which serves to reflect the signal beam. In this final project is designed, realized and measured at the antenna grid on GSM 900 MHz. This antenna is intended to be a media aids in strengthening the GSM signal reception to maximize the signal acquisition and connections